Numerical assessment of mass conservation on a MAC-type method for viscoelastic free surface flows - Martins, Fernando P. [UNESP]; Oishi, Cassio M. [UNESP]; Sousa, Fabricio S.; Cuminato, Jose A. (My University, 2012)
A numerical study of mass conservation of MAC-type methods is presented, for viscoelastic free-surface flows. We use an implicit formulation which allows for greater time steps, and therefore time marching schemes for advecting the free surface marker particles have to be accurate in order to preserve the good mass conservation properties of this methodology. We then present an improvement by using a Runge-Kutta scheme coupled with a local linear extrapolation on the free surface. A thorough study of the viscoelastic impacting drop problem, for both Oldroyd-B and XPP fluid models, is presented, investigating the influence of timestep, grid spacing and other model parameters to the overall mass conservation of the method. Furthermore, an unsteady fountain flow is also simulated to illustrate the low mass conservation error obtained.
Keywords: Benchmark results; Finite difference method; Free-surface flows; Mass conservation; Viscoelastic fluids; Fluid models; Fountain flow; Free surfaces; Free-surface flow; Grid-spacings; Implicit formulation; Local linear; Low mass; Mass conservation properties; Model parameters; Oldroyd-B; Time marching schemes; Time step; Visco-elastic fluid; Computational methods; Electronic publishing; Runge Kutta methods; Surfaces; Numerical methods